Does Depleting Self-Control Result in Poorer Vigilance Performance?. (May 2019) - Satterfield, Kelly; Harwood, Amanda E.; Helton, William S.; Shaw, Tyler H.
Objective: To investigate whether depleting self-control prior to vigilance results in a steeper vigilance decrement. Background: The resource-control theory of vigilance asserts that an inherent bias toward self-generated mind-wandering draws attentional resources away from the primary task. This study seeks to test whether depleting self-control, the potential mechanism of self-generated mind-wandering, results in poorer vigilance performance. Method: This study featured a between-subjects design where participants either completed a typing task that depleted self-control resources or a standard typing task that did not require self-control before performing a vigilance task. In the self-control depletion condition, participants typed a passage while omitting any "e" and "space" keys. In the standard typing task, participants typed the same passage without skipping any keys. Following both typing tasks, participants in both conditions completed an identical 12-min vigilance task. Results: Results demonstrated decreased accuracy and increased reaction times over time for both groups. Depleting self-control did not result in significant differences in accuracy, reaction time, nor a steeper vigilance decrement. Conclusion: These results provide evidence against resource-control theory and self-control as an explanation for vigilance, and provide further support for cognitive resource theory as the predominant explanation for vigilance impairments. Application: It is still unclear exactly what constitutes a "resource." A better understanding of the nature of these resources can help researchers and practitioners identify how they can be replenished, which could enhance human performance in situations requiring vigilance such as baggage screening.